2020
DOI: 10.1051/0004-6361/202037455
|View full text |Cite
|
Sign up to set email alerts
|

Molecular globules in the Veil bubble of Orion

Abstract: Strong winds and ultraviolet (UV) radiation from O-type stars disrupt and ionize their molecular core birthplaces, sweeping up material into parsec-size shells. Owing to dissociation by starlight, the thinnest shells are expected to host low molecular abundances and therefore little star formation. Here, we expand previous maps made with observations using the IRAM 30 m telescope (at 11″ ≃ 4500 AU resolution) and present square-degree 12CO and 13CO ( Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 105 publications
2
9
0
Order By: Relevance
“…That is, most globules are strongly compressed and become dense, but they are destroyed by shocks, and star formation activities are limited. This prediction for the future star formation of these globules is consistent with the prediction by Goicoechea et al (2020). (Goicoechea et al 2020).…”
Section: Effect Of Turbulencesupporting
confidence: 90%
See 3 more Smart Citations
“…That is, most globules are strongly compressed and become dense, but they are destroyed by shocks, and star formation activities are limited. This prediction for the future star formation of these globules is consistent with the prediction by Goicoechea et al (2020). (Goicoechea et al 2020).…”
Section: Effect Of Turbulencesupporting
confidence: 90%
“…The Extended Orion Nebula (M42) is photoionized by a massive star in the Trapezium cluster, θ 1 Ori C (e.g., O'Dell 2001;Simón-Díaz et al 2006). Using the IRAM 30m telescope, Goicoechea et al (2020) presented 12 CO and 13 CO (J = 2−1) maps of the "Veil bubble" driven by the strong wind emanating from θ 1 Ori C. They indicated the presence of ten CO "globules" blueshifted from the OMC and embedded in the expanding shell that encloses the bubble. These CO globules are small (R g 7100 AU), not massive (M g 0.3M ) and are moderately dense: n H 4.0 × 10 4 cm −3 (median values of the sample).…”
Section: Effect Of Turbulencementioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have revealed that star-forming clouds usually exhibit filamentary structures, within which a signifi-cant fraction of gravitationally bound dense cores and protostars are embedded (André et al 2013(André et al , 2014André 2017;Schneider et al 2012;Contreras et al 2016;Yuan et al 2019Yuan et al , 2020. There are also a fair amount of nonfilaments, e.g., globules, cometary, and extended structures (Bok & Reilly 1947;Bourke et al 1995a;Mäkelä & Haikala 2013;Goicoechea et al 2020), which either harbor a few young stars or are less opaque, less dense, with little or no star formation (Bourke et al 1995a,b;Reipurth 2008;Haikala et al 2010;Goicoechea et al 2020). However, the percentages and mass fractions of filaments and non-filaments in molecular clouds are still unclear.…”
Section: Introductionmentioning
confidence: 99%